An overview about Therapeutic uses, clinical efficacy, safety and classes of Retinoids and its efficacy for Treatment of skin aging - Suha Nadem Muhsin,; Ali Hasan, shireen; Makarim M.Ali Hassan, (University of Thi-Qar Journal of Science, 2023)
Abstract Skin aging has both underlying and extraneous factors. the outermost organ of the human body, the skin suffers from environmental damage to agents such as air pollution and cigarette smoking, the resulting skin aging is called extraneous aging, which is also known as photoaging or the exposure to sunlight via UV radiation. Retinoid refers to the synthetic and natural analogues of vitamin A. Retinoids are a class of compounds derived from vitamin A or showing structural and/or functional similarities to vitamin A. Retinoids as dermatological agents that are widely applied in cosmetics and effective against acne, psoriasis, skin aging, and other skin conditions. Their susceptibility to degradation is a limiting factor for their widespread use, In other words; retinoid concentration in cosmetics is restricted, and one particular form–retinoic acid, is banned due to safety reasons. These include retinol, retinal, tretinoin (retinoic acid), isotretinoin, and alitretinoin, etretinate, adapalene, bexarotene, tazarotene, and Trifarotene. The aim of this review is to introduce the different uses of different types of retinoid in cosmetic and dermatological treatments.Key words: Retinoids, skin, photoaging, vitamin A